The portrait of a lady - James, Henry (Penguin London, 1997)
The story centres on Isabel Archer, an attractive American whom circumstances have brought to Europe. Isabel refuses the offer of marriage to an English peer and to a bulldog-like New Englander, to fall victim to a worthless and spiteful man, who marries her for her fortune and ruins her life